The Iranian reception of Islam. Volume 2 : the non-traditionalist strands : collected studies in three volumes - Crone, Patricia, 1945-2015. (Leiden : Brill, 2016)
Patricia Crone's Collected Studies in Three Volumes brings together a number of her published, unpublished, and revised writings on Near Eastern and Islamic history, arranged around three distinct but interconnected themes. Volume 2, The Iranian Reception of Islam: The Non-Traditionalist Strands , examines the reception of pre-Islamic legacies in Islam, above all that of the Iranians. Volume 1, The Qurʾānic Pagans and Related Matters , pursues the reconstruction of the religious environment in which Islam arose and develops an intertextual approach to studying the Qurʾānic religious milieu. Volume 3, Islam, the Ancient Near East and Varieties of Godlessness , places the rise of Islam in the context of the ancient Near East and investigates sceptical and subversive ideas in the Islamic world. The Qurʾānic Pagans and Related Matters Islam, the Ancient Near East and Varieties of Godlessness
Front Matter / Hanna Siurua and Patricia Crone -- Kavād’s Heresy and Mazdak’s Revolt -- Zoroastrian Communism -- Khurramīs -- Muqannaʿ -- Abū Tammām on the Mubayyiḍa -- The Muqannaʿ Narrative in the Tārīkhnāma: Part I, Introduction, Edition and Translation / Patricia Crone and Masoud Jafari Jazi -- The Muqannaʿ Narrative in the Tārīkhnāma: Part II, Commentary and Analysis / Patricia Crone and Masoud Jafari Jazi -- Al-Jāḥiẓ on Aṣḥāb al-Jahālāt and the Jahmiyya -- Buddhism as Ancient Iranian Paganism -- A New Text on Ismailism at the Samanid Court / Patricia Crone and Luke Treadwell -- What Was al-Fārābī’s ‘Imamic’ Constitution? -- Al-Fārābī’s Imperfect Constitutions -- Pre-Existence in Iran: Zoroastrians, Ex-Christian Muʿtazilites, and Jews on the Human Acquisition of Bodies -- List of Patricia Crone’s Publications / Hanna Siurua -- Index of Names and Terms / Hanna Siurua.
Includes index.
Includes bibliographical references and inbdex.
Keywords: Islam -- Iran -- History; Islam; Iran; History